VD_FINDINFO HC / 2017 / 34 vom 9. Januar 2017 - VD Tribunal cantonal (2017)
TRIBUNAL DES PRUD'HOMMES, AUTORITÉ CANTONALE, PÉRIODE D'ESSAI, LICENCIEMENT ADMINISTRATIF | 336 CO, 20 LPers-VD, 21 al. 1 LPers-VD, 22 LPers-VD, 60 LPers-VD